Rapid brain MRI acquisition techniques at ultra-high fields - Setsompop, Kawin; Feinberg, David A.; Polimeni, Jonathan R. (NMR in biomedicine, 2016)
Ultra‐high‐field MRI provides large increases in signal‐to‐noise ratio (SNR) as well as enhancement of several contrast mechanisms in both structural and functional imaging. Combined, these gains result in a substantial boost in contrast‐to‐noise ratio that can be exploited for higher‐spatial‐resolution imaging to extract finer‐scale information about the brain. With increased spatial resolution, however, there is a concurrent increased image‐encoding burden that can cause unacceptably long scan times for structural imaging and slow temporal sampling of the hemodynamic response in functional MRI – particularly when whole‐brain imaging is desired. To address this issue, new directions of imaging technology development – such as the move from conventional 2D slice‐by‐slice imaging to more efficient simultaneous multislice (SMS) or multiband imaging (which can be viewed as “pseudo‐3D” encoding) as well as full 3D imaging – have provided dramatic improvements in acquisition speed. Such imaging paradigms provide higher SNR efficiency as well as improved encoding efficiency. Moreover, SMS and 3D imaging can make better use of coil sensitivity information in multichannel receiver arrays used for parallel imaging acquisitions through controlled aliasing in multiple spatial directions. This has enabled unprecedented acceleration factors of an order of magnitude or higher in these imaging acquisition schemes, with low image artifact levels and high SNR. Here we review the latest developments of SMS and 3D imaging methods and related technologies at ultra‐high field for rapid high‐resolution functional and structural imaging of the brain. Copyright © 2016 John Wiley & Sons, Ltd. Recent development trends in moving away from 2D imaging to simultaneous multislice (SMS) and 3D imaging have provided dramatic improvements in acquisition speed and SNR efficiency for high‐resolution imaging at ultra‐high field. SMS and 3D imaging can make better use of coil sensitivity information for parallel imaging acquisitions through controlled aliasing in multiple spatial directions. This has enabled unprecedented acceleration factors of an order of magnitude or higher, with low artifact levels and high SNR.